Development of yttrium phosphate based porous microspheres for radioembolisation therapy - Arafat, Abul (2022)
The principal focus for the materials developed in this thesis was for Radioembolisation therapy applications, particularly tailoring phosphate based glasses (PBG’s) formulations for the treatment of liver cancer. PBG’s have been widely considered in this study due to their fully resorbable, controlled degradation rates and biocompatible properties. Microspheres are gaining attraction as possible advanced materials, owing to their advantages over irregular shaped particles due to its better size, shape, higher surface area and improved flow characteristics. Phosphate glass microspheres containing yttrium oxide (Y2O3) are an area of particular interest in this thesis as Y2O3 has short half-life and been shown to significantly be efficient for improving chemical durability, which in turn is highly beneficial for selective internal radiation therapy (SIRT).